Genetic Epidemiological Studies of Diabetes Mellitus in Hospital Population of District Bahawalpur - Muhammad Waseem; Farhat Ullah; Romana Arshad (Universitas Pendidikan Indonesia (UPI), 2022)
Diabetes is considered a disease that is characterized by high glucose levels in the blood. Diabetes has become a global epidemic disease which is most common in developing countries. The aims are to provide an estimate of diabetes prevalence in the hospital population of district Bahawalpur. The study was carried out on 1000 Diabetic patients, Data was collected by a well-designed Questionnaire. In the statistical analysis, the percentage (%), Standard Error (S.E), mean (M), and Chi-Square tests were used. Out of 1000 Diabetic patients, 39.6% (396) were females and 60.4% (604) were males. The mean age was 51.57 ± 0.50 years in females and for the males, it was 47.99 ± 0.53. A greater number of patients belonged to the urban areas with 70.5% (705/1000) and Minimum belonged to Rural areas with 29.5% (295/1000). BMI recorded in the maximum range of 23-26.9 with 39.9% (399/1000) of the patients while it is recorded minimum the range of ≥27 with 10.1% (101/1000). By family history, much of the diabetic patients belonged to the consanguinity group with 35.7% (357/1000), while it was minimum in the out of cast 7.8 (78/1000). Type II Diabetes mellitus was more common with 64.2% (642/1000) and less common with 35.8% (358/1000). A more fetal onset of Diabetes occurs in the patients with Diabetic family history.